Beliefs and attitudes of health workers to influenza vaccination: a survey. (2nd December 2019) - King, Andrea; Doherty, Tracy; Quintyne, Keith Ian; Brabazon, Elaine
Abstract : Flu season has arrived, and with it comes the increased risk of health professionals infecting those under their care. It is vital, therefore, that barriers that may deter healthcare professionals from being vaccinated are addressed. Researchers at Ireland's Department of Public Health presents its fascinating findings about these obstacles and how to overcome them